The Influence of Sharia Accounting Knowledge and Family Environment on Interest in A Career in Sharia Financial Institutions - Maya Nurmawati; Amaliyah Amaliyah (eCo-Fin, 2024)
The interaction between family environment and sharia accounting knowledge can have a big impact on the larger socioeconomic environment. Increased awareness and education about the principles and benefits of Sharia banking have led to greater acceptance and adoption among Indonesians. This research aims to examine the effect of sharia accounting knowledge and family environment regarding interest in a career in sharia financial institutions. The method used a quantitative method using primary data using retrieval techniques samples using the Slovin method. obtained from a total of 66 respondents from the Sharia programme in Accounting Department at Pamulang University. The analysis in this research uses multiple linear regression analysis. This study reveal that Sharia Accounting Knowledge influences Career Interest in Sharia Financial Institutions. Family environment influences career interest in sharia financial institutions. The findings show that Sharia Accounting Knowledge and Family Environment simultaneously rely on Career Interests in Sharia Financial Institutions. This research line with theory of planned behavior which assumes that background education and knowledge influence action somebody and also proves that knowledge of Sharia economics and environmental of Family influence in a way positive career in the field service of Islamic finance institution The rapid growth of Sharia banking in Indonesia also need government support, increased public awareness, and sharia accounting knowledge are factors combined have positioned Indonesia as a key player in the global Islamic finance industry.